2018
DOI: 10.13168/cs.2018.0046
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Steel Slag With Variable Particle Size Distribution on the Workability and Mechanical Properties of Concrete

Abstract: The present research investigated the influence of steel slag (SS) with variable particle size on the workability and mechanical properties of concrete. Different SS size ranges (0-15 μm, 15-30 μm, 30-45 μm and 45-80 μm) were obtained by sieving and then were characterised by a laser particle size analyser and a scanning electron microscope (SEM). The slump, compressive strength, pore structures and thermal analysis were used to evaluate the effect of the SS particle size on cement and concrete properties. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Subsequently to their combination with cement, different pozzolans have diverse influences on the properties of cement based materials. For instance, steel slag decreased the workability of concrete [2], also WA decreased the workability, that extra water needed to be added [3]. On the other hand, mortar flow was slightly increased with increased in GP addition [4].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequently to their combination with cement, different pozzolans have diverse influences on the properties of cement based materials. For instance, steel slag decreased the workability of concrete [2], also WA decreased the workability, that extra water needed to be added [3]. On the other hand, mortar flow was slightly increased with increased in GP addition [4].…”
Section: Introductionmentioning
confidence: 98%
“…Despite of concrete importance as a construction building materials around the worlds because of widespread availability of its constituents, its versatility, its durability, and its adaptability, but it is side effects for environment concrete, use large volumes of raw materials that are quarried from the earth, their production requires a large amount of energy, and the manufacture of Portland cement emits a large amount of CO 2 [1]. The production of one ton of cement requires about 1.6 metric ton of raw materials [1][2][3]. So that, reusing waste constitutes substitute of cement as a supplementary cementitious materials, this materials is a by-products of other industrial processes or wastes like (Glass Powder (GP), Steel Slag Powder (SSP), and Wood Ash (WA)), an important challenge in order to reach a more sustainable environment.…”
Section: Introductionmentioning
confidence: 99%
“…When the dosage of the steel-slag powder was more than 10%, the strength clearly decreased [ 36 ]. In contrast to the incorporated steel slag in the15–30 μm and 30–45 μm ranges, the steel-slag particles with sizes of less than 15 μm and 45–80 μm were advantageous for the 7- and 28-day compressive-strength development of the concrete, especially at a low replacement ratio of up to 10% [ 37 ]. In conclusion, the mechanical properties of SPC are mainly focused on axial compressive and tensile behaviors, while the fracture properties of steel-slag-powder concrete are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Mortar and concrete with the addition of SS have shown improvement in fresh and hardened properties compared to regular specimens produced by conventional Ordinary Portland Cement. In the study of [10], SS with particle size between 30-45 μm and 45-80 μm were used to partially replace cement. Result showed that workability of fresh concrete increased with the increase in SS replacement ratio from 0 to 20%, due to the lower water absorption of SS and extra water to improve the fluidity of fresh concrete [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of [10], SS with particle size between 30-45 μm and 45-80 μm were used to partially replace cement. Result showed that workability of fresh concrete increased with the increase in SS replacement ratio from 0 to 20%, due to the lower water absorption of SS and extra water to improve the fluidity of fresh concrete [10]. Normally, the replacement of cement by SS has negative effect on mechanical properties of mortar and concrete when the replacement ratio of SS exceeds certain range.…”
Section: Introductionmentioning
confidence: 99%